Certificates № 00001 - Abdikarimova , Dinara (Innovation Science and Technology, 2025)
This certificate confirms that Professor Abdikarimova Dinara Rustamkhanovna, Doctor of Economic Sciences (DSc), is a member of the Editorial Board of the scientific journal "INNOVATION SCIENCE AND TECHNOLOGY", which specializes in science and technology as well as economic innovations. THE SCIENTIFIC-POPULAR ELECTRONIC JOURNAL "INNOVATION SCIENCE AND TECHNOLOGY HAS BEEN REGISTERED UNDER THE NUMBER C-5669633 BY THE AGENCY FOR INFORMATION AND MASS COMMUNICATIONS (AOKA) OF THE REPUBLIC OF UZBEKISTAN, EFFECTIVE FROM OCTOBER 9, 2024